Tracking Control for Polysolenoid Linear Motor Base-On Model Predictive Controller: A Comparative Study of Finite Control Set and Continuous Control Set (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, two predictive control methods, namely continuous control set MPC (CCS-MPC) and finite control set MPC (FCS - MPC), are applied to control Polysolenoid linear motors. These two approaches are based on the assumption that the voltage applied to the two windings on the stator of the motor is continuous or discontinuous. The method of choosing an objective function to ensure that the optimal problem always has a solution is also considered in both cases. Next, the prediction range guaranteeing the balance between the computing capability of the microcontroller and the advantages of each method is discussed. Finally, simulation results evaluate the system response to compare the performance of the two methods.